Projeto de cidade : comunicação, consumo e lógicas de produção - Oliveira, Adriana Lima de (2021)
The core of this thesis is the city, whose discussion is focused on both communication and consumption studies. The research objects are the cities of Lisbon (Portugal) and São Paulo (Brazil), framed to shed light on communication flows put into circulation both in the tourist and the real estate market, which, each one in turn, project the city idea / ideal. This way, Lisbon represents “the capital of tourism” and São Paulo “the capital of business”. These two territorial choices have taken into account the swift changes in urban and social landscapes from the point of view of an intense economic and political movement, and the admittance of these locations into a global investment system. The research question concerns how the emerging meanings, arising from the different discourses that lead the person to the consumption of/in the city, and address the ways of thinking and living the city in the general framework of the new communicational dynamics. To answer this question, we rely on the theoretical contribution of the concept of media bios proposed by Muniz Sodré (2002, 2014) that allows us to reflect on the urban space crossed by a new form of sociability that combines technology and the market. This way, we list as a general objective of this research paper to critically analyze the communication flows inscribed in the mediatized urban space aiming at unveiling the constitution of certain cartographies that project the city and propose corresponding ways of life. We have adopted as a method of investigation both a bibliographic and an empirical research with three observation frames: (i) media, (ii) thematic events and (iii) interviews. Data analysis has developed based on three conceptual categories inspired by Foucaultian studies: (i) discourse, (ii) biopolitics and (iii) governmentality. This trail from which we compose our analytical framework was made during a collection period that begins in 2018 in Lisbon and ends in 2020 in São Paulo. Therefore, this paper is part of the PPGCOM ESPM research line that studies the logics and production systems that are evident in the communicational processes and foundations. As a result, we come to a map where the different cities overlap — (in) visible; (in) complete and (in) common — and opens space for dialogue with literacy strategies, a condition for fostering a new form of consumption in the city and the justification for political and economic change. The pandemic has accentuated consumption attached to technology, and notions and practices related to mobility and access have become articulators of the city ways of life. In this sense, we conjecture the emergence of the communicational city and its reading through literacies — media, advertising and space — as an opportunity for the promotion of a humane city that overlaps the different nomenclatures used to qualify or disqualify the territory: the global city, the creative city, the smart city or, even, the sustainable city.